The Influence of Leadership, Organizational Citizenship Behavior (OCB), and Organizational Culture On Employee Performance - Ani Wijayanti; Eryco Muhdaliha; Setyani Dwi Lestari (PT. Publikasiku Academic Solution, 2023)
This study examines the impact of leadership, Organizational Citizenship Behavior (OCB), and organizational lifestyle on overall employee performance. The study was conducted in Bitung Metropolis at KPP Pratama Bitung, and a total of 103 employees of KPP Pratama Bitung were interviewed. Research Design, Data, and Methodology: The type of research conducted is explanatory research with a general sampling approach. Fact-gathering was done through a questionnaire using the Likert scale model processed with the Microsoft Excel 2019 software program and the SPSS 25 model. The validity test and the reliability test of the research tool used the SPSS correlation coefficient significance test and the significance test. Cronbach Alpha (A) SPSS Statistical Examination. Information analysis strategy with multiple regression evaluation. Findings: This study provides findings demonstrating that leadership, organizational citizenship behavior (OCB), and organizational lifestyle simultaneously positively impact employee performance, while leadership, organizational citizenship behavior (OCB), and organizational lifestyle partially positively impact worker performance. Conclusion: Implementation of the strategy or steps in this study is intended to guide and motivate an organization to successfully apply leadership, organizational civic behavior (OCB), and organizational culture to improve employee performance.